Educational Culture and Popular Culture: Case Study Festivals in Sai Gon South International School, Ho Chi Minh City - Nguyen, Huyen (American Scientific Research Journal for Engineering, Technology, and Sciences, 2019)
Education, whose main object is pulpils and students – the young living in a continuosly connected environment, is characterized by endless diversity, regular interactions, the requirement for considering and examining the relation and influence of popular culture on education is essential and inevitable because “Whether we like it or not, popular culture touches all of our lives and the lives of our students. As educators, we cannot ignore popular culture”[9]. SaiGon South International School (located at 78 Nguyen Duc Canh Street, Tan Phong ward, District 7, Ho Chi Minh City, Vietnam) is one of the International Schools established earliest in Vietnam (over 20 years). This is the school following the curriculum of the United States situated in the East manifesting a multicultural environment with its objectives to create global citizens, who have quick responses to the changes of the times; moreover, popular culture is most focused and integreated into education and the curriculum of the school. In this paper, inheriting from previous studies and research on the relation between educational culture and popular one of some eminent scholars such as Diana Silbermanoo-Keller, Zvi Bekerman, Henry A. Giroux, and Nicholas C. Burbules; Jessica Wilson; John Morgan; L. Harklau and J. Zuengler; Owen Roberts; Robert Petrone; William Clapton as well as applying the structural chart of popular culture house created by John G. Jachbar, Kevin Lausé 1992 into the topic “Educational culture and popular culture: Case study Festivals in Sai Gon South International School, Ho Chi Minh City”, the writer analysed the values of educational culture reflected in mass festivals celebrated at SaiGon South International School by using opposite pairs like individual : collective; rests : studies; mass culture : elite culture; particularity : universality.